Pengaruh Independensi, Peran Auditor Internal dan Profesionalisme Auditor Internal terhadap Efektivitas Penerapan Sistem Pengendalian Internal pada PT. Perkebunan Nusantara IV PKS Adolina Perbaungan - Futri Dewani Purba; Duma Megaria Sihite; Ivo Silitonga (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to examine the influence of independence, role, and professionalism of internal auditors on the effectiveness of internal control system implementation, both partially and simultaneously. The research was conducted at PT. Perkebunan Nusantara IV PKS Adolina Perbaungan. The study employed multiple regression analysis using SPSS (Statistical Package for the Social Sciences) version 25. The population of this study consisted of 84 employees from 7 departments within PT. Perkebunan Nusantara IV PKS Adolina Perbaungan. The entire population was used as the sample through a saturated sampling method. The data used in this research is quantitative, measured using a Likert scale and converted into interval data. The results of the study show that, partially, the independence of internal auditors does not have a positive and significant effect on the effectiveness of internal control system implementation. In contrast, the role and professionalism of internal auditors have a positive and significant effect on the effectiveness of internal control system implementation when examined individually. Furthermore, the findings also indicate that these variables simultaneously have a significant effect on the effectiveness of internal control system implementation.